Solid Confinement of Quantum Dots in ZIF‐8 for Efficient and Stable Color‐Conversion White LEDs. Issue 7 (22nd March 2017) - Ying, Wen; Mao, Yiyin; Wang, Xiaobing; Guo, Yi; He, Haiping; Ye, Zhizhen; Lee, Shuit‐Tong; Peng, Xinsheng
Abstract: The powder form and low photoluminescence quantum yield (PLQY) of fluorescent metal–organic frameworks (MOFs) present a serious obstacle to fabricating high‐efficiency film‐like lighting devices. Here, we present a facile way to produce thin films of CdSe x S1− x /ZnS quantum dots (QDs)@ZIF‐8 with high PLQY by encapsulating red, green, and blue CdSe x S1− x /ZnS QDs in ZIF‐8 through a one‐pot solid‐confinement conversion process. The QDs@ZIF‐8 thin film emits warm white light with good color quality and presents good thermal stability and long‐term durability. Abstract : Let there be light : Solid‐confinement conversion provides a facile way to in situ encapsulate semiconductor fluorescent quantum dots (QDs) into a porous, thermally stable, and hydrophobic ZIF‐8 thin film for high‐performance white light‐emitting diodes (LEDs). The resulting QDs@ZIF‐8 thin film shows a photoluminescence quantum yield of 86 %, good thermal stability, and long‐term durability in air.